SYSTEMIC LUPUS ERYTHEMATOSUS COMPLICATED WITH CASTLEMAN DISEASE : A CASE REPORT - Khurshid, Ahsan; Abbas, Anum; Iqbal, Suhail; Khan, Raheel (Journal of Ayub Medical College Abbottabad, 2026)
Castleman disease is a rare nonclonal heterogeneous group of diseases involving lymphoid tissue. It often simulates other inflammatory conditions and malignancies. Systemic lupus erythematosus, being a multisystem inflammatory disorder, shares many features with Castleman disease. Here, we report a similar case of a middle age female who was initially diagnosed as SLE with lupus nephritis, for which she was put on steroids and immunosuppressants. After commencing treatment, her symptoms resolved and she remained in remission for some period. However, her condition was complicated with Castleman disease later on. For diagnostic and therapeutic purpose, she underwent lymph node resection and to our surprise, her condition improved.